Plantas tóxicas do município de Cananéia: um enfoque etnobotânico - Oler, Juliana Rodrigues Larrosa [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Among several sites in Brazil, where the local human community develop a consistent knowledge on the environment they live, there is Cananeia local authority in south coast of Sao Paulo. The history of Cananeia is presented as an ancient human occupation, which, nowadays, culminates in 12000 habitants that survive from tourism and fishing. Considering the great importance of the knowledge about plant toxicity, the objective of this work is to develop a study with the residents and its focus is their acquaintance with toxic plants, which occur on contiguous areas. After a preliminary recognition field work, the local authority under study was subdivided into two areas for sampling, characterized by the different levels of human occupation: (A) Island area, more occupied, and (B) Continental area, less occupied. The semi-structured interviews were conducted in both areas according to the “snow ball” method, due to the specifically interest of making comparisons. The plant species cited in the interviews were collected, herborized and identified. One proceeded quali- and quantitative analysis in order to elucidate differences between the studied areas, to establish relations among age/sex of the habitants, the cited species diversity and the practice of knowledge transmission. Were carried out 90 interviews (47 in island, 43 in continent) in which the habitants have cited 137 ethno-species. Both communities are much alike, although the manly differences were presented by the occupation and the uses of the toxic plants. At the island, were interviewed three key-informers, this fact that has not happened at the continent. It was not noticed significant statistical difference between the diversity of toxic plants knew by the habitants of both areas, but a huge dissimilarity was found. The most cited plants, especially the ornamental ones, at both areas are scientifically... (Complete abstract click electronic access below)

Dentre as muitas áreas no Brasil nas quais comunidades locais desenvolvem conhecimento refinado sobre o ambiente onde habitam está o município de Cananéia, localizado no litoral sul de São Paulo. Cananéia apresenta uma história de ocupação humana muito antiga, sendo que atualmente o município conta com aproximadamente 12000 habitantes que sobrevivem basicamente do turismo e da pesca. Considerando a importância do conhecimento sobre a toxicidade das plantas este trabalho tem por intuito realizar um estudo etnobotânico com os moradores, sendo o foco da pesquisa o conhecimento dos moradores sobre as plantas tóxicas encontradas no local. Para amostragem, após viagem de campo preliminar para aproximação e reconhecimento da área, o município foi dividido segundo a intensidade de antropização em dois núcleos populacionais distintos, sendo: (A) Zona insular do município, mais antropizada e (B) zona continental, menos antropizada. Com o intuito de comparar o conhecimento nas duas áreas foram coletados dados (sociais e sobre as plantas) com os moradores através do método da “bola de neve” usando entrevistas semi-estruturadas. As espécies vegetais citadas foram coletadas, herborizadas e identificadas. Análises qualitativas e quantitativas foram realizadas com objetivo de estabelecer relações entre idade/sexo dos moradores e diversidade de espécies conhecida, formas de transmissão do conhecimento, diferenciações entre o conhecimento nas diferentes áreas, e elaboração da ordenação das plantas mais citadas. Foram entrevistados 90 moradores (47 ilha e 43 continente) que citaram um total de 137 etnoespécies. As comunidades das duas áreas são bastante parecidas, diferenciando-se principalmente pela ocupação e pelo uso das plantas tóxicas citadas. Na ilha foram entrevistados três informanteschave, fato que não ocorreu no continente... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ecologia humana; Plantas venenosas; Conhecimento ecológico local; Ethnobotany; Toxic plants